Fabricating customized hydrogel contact lens - Childs, Andre (Sci Rep, 2016)
Contact lenses are increasingly used in laboratories for in vivo animal retinal imaging and pre-clinical studies. The lens shapes often need modification to optimally fit corneas of individual test subjects. However, the choices from commercially available contact lenses are rather limited. Here, we report a flexible method to fabricate customized hydrogel contact lenses. We showed that the fabricated hydrogel is highly transparent, with refractive indices ranging from 1.42 to 1.45 in the spectra range from 400 nm to 800 nm. The Young’s modulus (1.47 MPa) and hydrophobicity (with a sessile drop contact angle of 40.5°) have also been characterized experimentally. Retinal imaging using optical coherence tomography in rats wearing our customized contact lenses has the quality comparable to the control case without the contact lens. Our method could significantly reduce the cost and the lead time for fabricating soft contact lenses with customized shapes, and benefit the laboratorial-used contact lenses in pre-clinical studies.